2021
DOI: 10.1096/fj.202100032r
|View full text |Cite
|
Sign up to set email alerts
|

The role of nuclear receptor 4A1 (NR4A1) in drug‐induced gingival overgrowth

Abstract: Drug‐induced gingival overgrowth (DIGO) is a side effect of cyclosporine A (CsA), nifedipine (NIF), and phenytoin (PHT). Nuclear receptor 4A1 (NR4A1) plays a role in fibrosis in multiple organs. However, the relationship between NR4A1 and DIGO remains unclear. We herein investigated the involvement of NR4A1 in DIGO. In the DIGO mouse model, CsA inhibited the up‐regulation of Nr4a1 expression induced by periodontal disease (PD) in gingival tissue, but not that of Col1a1 and Pai1. We detected gingival overgrowth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…We previously reported that Spock1 -Tg mice exhibit gingival overgrowth in the absence of periodontal inflammation due to the promotion of epithelial-to-mesenchymal transition by SPOCK-1 overexpression ( Alshargabi et al, 2020 ). Generally, gingival or periodontal inflammation promotes gingival thickening in patients with DIGO ( Sousa et al, 2011 ; Okanobu et al, 2017 ; Hatano et al, 2021 ). To confirm whether periodontal inflammation enhanced gingival overgrowth related to SPOCK-1 overexpression, Spock1 -Tg and WT mice were subjected to experimental periodontitis via placement of a silk ligature ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that Spock1 -Tg mice exhibit gingival overgrowth in the absence of periodontal inflammation due to the promotion of epithelial-to-mesenchymal transition by SPOCK-1 overexpression ( Alshargabi et al, 2020 ). Generally, gingival or periodontal inflammation promotes gingival thickening in patients with DIGO ( Sousa et al, 2011 ; Okanobu et al, 2017 ; Hatano et al, 2021 ). To confirm whether periodontal inflammation enhanced gingival overgrowth related to SPOCK-1 overexpression, Spock1 -Tg and WT mice were subjected to experimental periodontitis via placement of a silk ligature ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Plaque control is recommended for the treatment of DIGO. Most importantly, CsA, which is reported to induce frequent DIGO in human and mouse models ( Okanobu et al, 2017 ; Hatano et al, 2021 ), is known to inhibit CN/NF-AT signals. Therefore, we hypothesized that other factors that promote EMT cooperatively contributed to the development of DIGO and focused on the involvement of inflammation and NF-AT signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations